Arginase deficiency in Mexico: Insights from the experience of a metabolic reference center - M. Vela-Amieva; C. Fernández-Lainez; S. Guillén-López; L. López-Mejía; M.A. Alcántara-Ortigoza; A. González del Angel; L. Fernández-Hernández; M.E. Reyna-Fabián; B. Estandía-Ortega; I. Ibarra-González; S.W. Ryu; H. Lee (Molecular Genetics and Metabolism Reports, 2025)
Arginase deficiency (ARG1d) is an inborn error of metabolism caused by pathogenic variants in ARG1 gene, which causes a defective hydrolysis of arginine (Arg) to urea and ornithine. The molecular landscape of ARG1d in Mexico is poorly known. In this study, we present for the first time the clinical and genotypic overview of the largest cohort of ARG1d in Mexico. A retrospective analysis of the medical records of 24 ARG1d patients from a historical cohort of individuals with inborn errors of intermediary metabolism (1994–2024) from the National Institute of Pediatrics in Mexico City, was performed. Clinical, demographical, biochemical, anthropometric and molecular data were investigated in two moments, at diagnosis and at the last follow-up evaluation. It was found that only 7/24 patients were diagnosed by newborn screening (NBS). Additionally, we highlight the presence of the Portuguese NM_000045.4(ARG1):c.61C>T or p.(Arg21*) variant as the most frequent cause of ARG1d in Mexico, carried by 27.7 % of the patients. Our findings emphasize the debilitating and progressive nature of ARG1d, the prolonged diagnostic odyssey experienced by the patients (6.7 years), and the importance of training healthcare professionals to recognize the clinical features suggestive of the disease. We also underscore the critical need to advance early detection through expanded NBS in our country, as the early-diagnosed patients exhibited less severe outcomes and improved nutritional status compared to late-diagnosed ones. It was also noted that Mexican ARG1d patients have significant difficulties adhering to current nutritional treatment, and access to ammonium scavengers, thus other therapeutic options could be desirable.